Effectiveness of Instructional Communication of Mahārah Al-Kalām at Sultan Idris Education University - Yulia, Fatma; Ali Hasan, Elsayed Makki Elbishr; Bahri, Andini Nur; Fiqiyah, Maskanatul; Taufiq, Muhammad (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2024)
Studying mahārah al-kalām, or Arabic speaking skills, is fundamental to the Arabic department curriculum. Effective instructional communication between teachers and lecturers is crucial for successful learning outcomes. This study utilizes a mixed-method approach combining quantitative and qualitative research methodologies to assess the effectiveness of instructional communication in mahārah al-kalām at Sultan Idris Education University, Malaysia. The findings reveal a high level of effectiveness in instructional communication, with an overall score of 90.36%. The primary factors influencing the effectiveness of instructional communication include the lecturer’s credibility, which encompasses expertise, trustworthiness, and attractiveness. This study contributes to the field of Arabic language education by emphasizing the importance of effective instructional communication in enhancing mahārah al-kalām learning outcomes. The results provide valuable insights for Arabic language educators, offering a basis for developing strategies to improve teacher-student interactions. For future research, exploring additional competencies, such as cultural and linguistic aspects, is recommended to achieve a more comprehensive understanding of mahārah al-kalām instruction. By addressing these areas, educators can foster a richer and more effective learning environment, contributing to the overall quality of Arabic language education.